Potential of Endophytic Bacteria from Roots Bangun-bangun (Couleus amboinicus Lour) Plant as Phosphate-solubilizing Agents - Lestari, Dwi Endah; manalu, kartika; nasution, rizki amelia (LenteraBio : Berkala Ilmiah Biologi, 2023)
Endophytic bacteria are bacteria that reside in plant tissues without causing disease. Endophytic bacteria are known to have the ability to solubilize phosphate which is an important nutrient for plant growth. This study aims to determine the potency of plant root endophytic bacteria (Coleus amboinicus Lour) in solubilize phosphate by five stages, namely isolation, morphological characterization, testing the ability of endophytic bacteria to solubilize phosphate, gram staining and biochemistry. The results obtained were 13 isolates of endophytic bacteria from the roots of the plant (C. amboinicus Lour), nine of which had the potential to solubilize phosphate which were identified as Micrococcus, Bacillus and Pseudomonas. BE4 isolate from the genus Pseudomonas has a high ability to dissolve phosphate with a phosphate solubilizing index value of 4.1 mm.